Comparative Analysis of Somatic Parameters and Movement Quality in Novice and Experienced CrossFit Athletes - Piotr Sporek; Mariusz Konieczny (Central European Journal of Sport Sciences and Medicine)
In this study, fifty active CrossFit athletes were divided into beginner (n=25, mean age 24.8±5.2 years) and experienced groups (n=25, mean age 25.1±4.9 years) to assess injury risk, body fat distribution, and functional movement quality at different levels of experience. All participants attended training sessions five times a week and were preparing for competitions, training CrossFit at a competitive level, with the beginner group having up to 2 years of CrossFit training and the experienced group having 4-6 years of training. We involved fifty active CrossFit athletes, divided into beginner and experienced groups, in our study. The athletes in the beginning group (n=25, mean age 24.8±5.2 years) had no more than 2 years of training experience, while the athletes in the experienced group (n=25, mean age 25.1±4.9 years) had between 4-6 years of training experience. All participants attended training sessions five times a week and were preparing for competitions, training CrossFit at a competitive level. Both groups were evaluated for skinfold thickness and body fat percentage using appropriate measurement techniques, while functional movements were assessed separately using the Functional Movement Screen (FMS) Kit system and protocol. The results indicated that the experienced group demonstrated significantly higher overall FMS scores (U = 71.5, p < .001, r = 0.67), suggesting better functional movement patterns and potentially lower injury risk. They also exhibited higher body density and lower body fat percentages (U = 126, p < .001, r = 0.51) compared to the beginner group, which had higher skinfold thickness measurements in the breast, abdominal, and thigh areas. The findings of the study suggest that with increased experience in CrossFit training, athletes tend to have lower body fat, especially in the lower body, and exhibit improved functional movement quality. These improvements in movement efficiency potentially decrease the risk of injury, highlighting the benefits of long-term participation in high-intensity CrossFit training.